A Study of Some Biochemical Parameters in COVID-19 Patients with Diabetes Mellitus: Comparative Study - Asmaa Sattar Abd; Izzat Al-Rayahi (Journal of Techniques)
COVID-l9 is considered a global health emergency, this disease affects all individuals and its symptoms are similar to the common cold. The purpose of this study is to compare diabetic and non-diabetic patients in some biochemical tests of patients infected with COVID-l9. Of the l20 patients included in the study, 7l patients were males (59.l7%) and 49 were females (40.83%). The study showed that the highest percentage was in males with diabetes (63.33%), followed by non-diabetics (55.00%), without significant difference. As for the age group, most patients were over 50 years, and it was most common among non-diabetics in addition to diabetes. Mean glucose was significantly different between the diabetic group and the non-diabetic group. For the diabetic group, the mean blood sugar was 229.22 ± 82.25mg/dl, while the mean blood sugar in the non-diabetic group was l32.25 ± 44.08 mg/dl. In addition, there was a significant difference in mean HbA1c between the diabetic and non-diabetic groups p < .001. For the diabetic group, the mean HbA1c was 7.5l ± l.27 %, but in the non-diabetic group, the mean HbA1c was 5.41 ± 0.73%. While there was a significant difference between the two groups with and without diabetes in the mean ferritin ratio p < .00l. For the diabetic group, the mean serum ferritin was 638.78 ± 327.78 ng/ml, although in the non-diabetic group, the mean serum ferritin was 393.74 ± 330.83 ng/ml. There were no significant differences between the diabetic and non-diabetic group in the mean of D-dimer, urea, creatinine and uric acid, in the diabetic groups, the mean was 6.00 ± 5.80 ug/ml, 86.02 ± 64.27 mg/dl, 1.64+1.45mg/dl and 5.37 ± 3.11mg/dl, respectively. While in the non-diabetic group, the mean was 5.82 ± 5.76 ug/ml, 74.68 ± 68.27mg/dl, 1.88 ± 2.62 mg/dl, and 4.86 ± 2.62 mg/dl, respectively.